A new species of the genus Lepidocyrtus Bourlet and a new record of Seira delamarei Jacquemart (Collembola: Entomobryidae) from the east coast of India - Zhang, Feng; Chatterjee, Tapas; Chen, Jian-Xiu (Zootaxa, 2009)
A new species, Lepidocyrtus (Lanocyrtus) absens sp. nov., and a new record, Seira delamarei Jacquemart, 1980, both from intertidal zone of the east coast of India are described. The complete dorsal chaetotaxy on each tergite, including Schaetae and microchaetae, is exhaustedly explored in L. absens sp. nov.; s-chaetae d1 and d2 on lateral Abd. III and median sensillum on Abd. V, setae Ll and im on Abd. III, and setae C1p, pe and s on Abd. IV are absent. The ciliate basal seta and 2 sublobal hairs on maxillary outer lobe, vestigial seta r and ciliate setae a1–5 on labium, and elongate median inner tooth on unguis are also diagnostic features of the new species. The tropical species S. delamarei is recorded for the second time from Asia besides Thailand.